Relative improvements between roads and railways and economic performance: a panel data analysis - Zheng, Qing Yuan; Law, Teik Hua; Wong, Shaw Voon; Ng, Choy Peng (Elsevier, 2024)
Prior studies indicate that expanding the length of roadways and railways has a beneficial effect on economic performance. Nevertheless, the requirement for land transport infrastructure, which offers different degrees of accessibility and mobility, to facilitate economic expansion differs based on a country's stage of development. The present study has two objectives. Firstly, it is essential to ascertain the required investment for different types of land transport infrastructure to facilitate different stages of economic performance. Secondly, the objective is to examine the impact of different forms of land transportation infrastructure on economic performance by means of urbanization and exports. To highlight these concerns, a fixed-effects panel linear regression analysis was conducted on a panel consisting of 50 countries spanning the years 1980–2018. In countries with lower levels of urbanization and exports, improvements to road infrastructure, especially roads with high accessibility, are of greater importance for economic performance compared to the improvement of railways. Nevertheless, as urbanization and exports rise, the comparative impact of improvements in road infrastructure on economic performance in relation to improvements in railway infrastructure diminishes. Railway improvements have a more significant effect on economic performance compared to road improvements, owing to increased urbanization and export rates. During these stages of development, high-mobility roads are more crucial for economic performance compared to high-accessibility roads. The conclusion of the research examined a variety of policy recommendations derived from our findings, which are applicable to different levels of urbanization and exports.